The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s13237-021-00350-7
|View full text |Cite
|
Sign up to set email alerts
|

Male meiosis and pollen morphology in diploid Indonesian wild bananas and cultivars

Abstract: Breeding of banana is hampered by its genetic complexity, structural chromosome rearrangements and different ploidy levels. Various scientific disciplines, including cytogenetics, linkage mapping, and bioinformatics, are helpful tools in characterising cultivars and wild relatives used in crossing programs. Chromosome analysis still plays a pivotal role in studying hybrid sterility and structural and numerical variants. In this study, we describe the optimisation of the chromosome spreading protocol of pollen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…The high pollen viability for tetraploid bananas is also uncommon since Fortescue and Turner (2004) showed that tetraploids of Indian and Australian origin had pollen viability of 28% and 29%, respectively. The high level of pollen viability of diploid Rejang has similar observations by Fortescue and Turner (2004) that indicated pollen viability of 84% of diploid M. acuminata and confirmed by Ahmad (2021) that demonstrated pollen viability of 77.7% from Rejang diploid. Since the frequency of viable pollen in a viability test indicates the fertility level in bananas (Fortescue and Turner, 2004), this result shows that the diploid natural cultivar of "Pisang Rejang" and its tetraploid and mixoploid derivative is amenable for a breeding parent.…”
Section: Discussionsupporting
confidence: 76%
“…The high pollen viability for tetraploid bananas is also uncommon since Fortescue and Turner (2004) showed that tetraploids of Indian and Australian origin had pollen viability of 28% and 29%, respectively. The high level of pollen viability of diploid Rejang has similar observations by Fortescue and Turner (2004) that indicated pollen viability of 84% of diploid M. acuminata and confirmed by Ahmad (2021) that demonstrated pollen viability of 77.7% from Rejang diploid. Since the frequency of viable pollen in a viability test indicates the fertility level in bananas (Fortescue and Turner, 2004), this result shows that the diploid natural cultivar of "Pisang Rejang" and its tetraploid and mixoploid derivative is amenable for a breeding parent.…”
Section: Discussionsupporting
confidence: 76%
“…Chromosome associations were also investigated in early prophase I cells, specifically at pachytene using DAPI, a blue fluorescing DNA-specific stain, to reveal chromosome details (see Ahmad et al, 2021) and FISH using telomeric probes. At this stage, the telomeres were labelled using rhodamine-labelled synthetic oligonucleotides (5 0 TELO1F-FLUORO-CCC TAA ACC CCT AAA CCC TAA ACC CTA AAC CCT AAA 3 0 and 3 0 TELO1R-RHOD-CCC TAA ACC CTA CCT AAA CCC TAA ACC CTA AAC CCT AAA 5 0 , Life Technologies).…”
Section: Pairing Investigation Using Fish With Centromeric and Telome...mentioning
confidence: 99%
“…2022 ). Diploid Musa enabled normal meiotic chromosome behaviour with bivalent chromosome pairs and normal balanced genomic segregation, resulting in fertile pollen ( Damaiyani and Hapsari 2018 ; Ahmad et al . 2021 ).…”
Section: Discussionmentioning
confidence: 99%